Efficacy and safety of high-voltage versus standard-voltage pulsed radiofrequency ablation for patients with neuropathic pain: protocol for a systematic review and meta-analysis - Zheng Wang; Yitong Jia; Yanhui Ma; Tengteng Wang; Kunpeng Feng; Guang Feng; Tianlong Wang (BMJ Open)
Introduction Pulsed radiofrequency (PRF) ablation is commonly used for the treatment of neuropathic pain (NP). However, it is unclear whether increasing the output voltage of PRF can safely improve its efficacy. This study aims to compare the efficacy and safety of high-voltage PRF ablation and standard-voltage PRF ablation for the treatment of patients with NP.Methods and analysis We will search PubMed/MEDLINE, EMBASE, Web of Science, the Cochrane Library, conference proceedings for relevant abstracts, clinical trials registers (ClinicalTrials.gov) and the WHO’s International Clinical Trial Registry Platform (from the date of inception until 15 March 2022). Only randomised controlled trials will be included. Two reviewers (YJ and GF) will independently perform study screening and selection, data extraction, risk-of-bias assessment and quality-of-evidence assessment. The primary outcome of this meta-analysis will be the efficiency rate in patients with NP. The secondary outcomes will include numeric rating scale score, visual analogue scale score, time to take effect, rescue drug dosage, quality of life using the health questionnaire (SF-36) and the incidence of adverse events. Meta-analyses will be conducted using standard meta-analysis software (RevMan V.5.3, The Nordic Cochrane Center, The Cochrane Collaboration, Copenhagen, Denmark).Ethics and dissemination The requirement for ethical approval was waived as our systematic review will be based on the published literature. The results of this study will be submitted to a peer-reviewed journal.PROSPERO registration number CRD42022297804.